From Etymology to Praxis: An Exploration of the Concept of Accompaniment in the Educational Context - EL MAKKAOUI , El Mostapha (Revue Internationale du Chercheur, 2025)
This article provides an in-depth exploration of the concept of support ("accompagnement") in vocational training, starting from its etymological and semantic roots to analyze its different dimensions, objectives, and practices. It highlights the complexity of the support relationship, the tensions between institutional requirements and learner autonomy, as well as the postures that facilitators must adopt. The article also presents an overview of the different models and forms of support, ranging from tutoring to mentoring via coaching and counseling, highlighting their specificities and complementarities. In conclusion, it emphasizes the importance of support as a transformative process that promotes the autonomy, responsibility, and socialization of learners.